IMPACT OF PERCEIVED ORGANIZATIONAL SUPPORT ON JOB SATISFACTION: A SEQUENTIAL MEDIATION - Alam, Mehboob; Gul, Fozia; Syed Intasar Hussain Kazmi (Journal of Arts & Social Sciences, 2022)
Current study investigates importance of POS and its related benefits on JS with sequential medication. Data is collected from three government universities of Lahore, Punjab, Pakistan. Total respondents were 429 from three public sector universities. Results of study demonstrated constructive and significant impact on JS (job satisfaction). Sequential mediation of IM and EM has also been tested. Results showed positive and significant impact of IM & EM in the relationship. Time horizon which was used is cross sectional, with sampling technique of stratified random sampling. To collect data, questionnaire survey (self-administrated) was used among the employees of three public sector universities. To analyses data, SPSS & Process by Hayes was used. In analysis descriptive tests like reliability, frequencies, mean, SD, correlation, and statistical technique for hypothesis testing, mediation analysis used. This study contributed to existing literature of POS and adds value to existing practices by examining theoretical model of sequential mediation that not used in any sector in Pakistan. This also explored that POS is an important indicator for job satisfaction through sequential mediation of IM and EM.